Preparation method and application of dopamine hydrochloride modified cerium oxide core-shell abrasive

The preparation method of modifying the oxide nuclear shell abrasive by dopamine hydrochloric acid solves the problem of low abrasive removal rate and poor water solution in the existing glass polishing method, and achieves high -efficiency and stable glass polishing effects.

CN119081653BActive Publication Date: 2025-01-24INNER MONGOLIA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411533727.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-24
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

In the existing glass polishing methods, the removal rate of the abrasive is low and the water solubility of the nano-absorbing is low, resulting in poor polishing efficiency.

Method used

The preparation method of modifying oxide nuclear shell abrasives is used to use silicic acid tetrachide, hexxial alkyl tritenium bromide, and ammonia water to prepare silicon dioxide microfilling. Form a stable nano -nano -nano -nano abrasive to improve its decentralized stability in the polishing fluid.

Benefits of technology

制备得到的氧化铈核壳纳米磨料尺寸可调,具有高抛光去除率和高度亲水性,显著提高了玻璃抛光的效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119081653B_ABST
    Figure CN119081653B_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a dopamine hydrochloride modified cerium oxide core-shell abrasive, comprising the following steps: adding water to a cerium salt until the cerium salt is completely dissolved, taking out a silica powder with a mass ratio of cerium salt to silica powder of (0.5:1)-(7:1), ultrasonically dispersing the powder in anhydrous ethanol to obtain a dispersion; mixing the dispersion with a hexamethylenetetramine aqueous solution and a cerium salt aqueous solution, heating and stirring the dispersion in an oil bath to obtain a mixed solution, centrifuging the mixed solution, washing with deionized water and anhydrous ethanol, and drying the mixed solution to obtain a mixed solid, calcining the mixed solid to obtain a cerium precursor; dispersing the cerium precursor in a mixed solution obtained by deionized water and ethanol, slowly adding dopamine hydrochloride and a buffer solution, stirring the solution, centrifuging, washing, and drying the solution to obtain a cerium precursor; and preparing a polishing liquid using the abrasive to obtain a removal rate of 0.1458 mg / min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of rare earth materials, and in particular to a preparation method and application of a dopamine hydrochloride modified cerium oxide core-shell abrasive. Background Art

[0002] With the advancement of modern electronic technology, the requirements for the surface roughness of glass surface quality are constantly increasing. The transparency, refractive index and surface quality of glass have become one of the important indicators for evaluating glass. The commonly used glass polishing methods currently include chemical mechanical polishing, laser polishing, fire polishing, acid polishing, etc. Among them, mechanical polishing is widely used because it is applicable to many types of glass. The key to chemical mechanical polishing (CMP) lies in the selection of polishing abrasives. Cerium oxide has a relatively moderate hardness and can bring a good polishing effect to glass through "soft polishing and hard polishing". At the same time, because the Ce element has multiple valence states and is easy to transform between different valence states, it promotes the formation of a hydrated softening layer on the glass surface, improves the removal rate, and has significant advantages in glass polishing.

[0003] The physical and chemical properties of abrasive particles, such as composition, structure, morphology and surface state, have a great influence on the material removal rate of the abrasive and the surface quality after polishing. Generally speaking, physical and chemical methods are used to functionalize the abrasive surface to overcome the agglomeration problem and improve the reactivity of the abrasive. In the existing technology, the removal rate is still low; and due to the low water solubility of nano-abrasives, the suspension is unstable, which ultimately leads to poor polishing efficiency.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The first purpose of the present invention is to provide a method for preparing a dopamine hydrochloride modified cerium oxide core-shell abrasive. The preparation method has a simple route and is easy to form a stable core-shell material. At the same time, the process makes full use of the hydrophilic molecular activity of dopamine to improve the dispersion stability of CeO2 abrasive in the polishing liquid. The prepared cerium oxide core-shell nanoabrasive has adjustable size and high polishing removal rate.

[0006] The second purpose of the present invention is to provide a method for preparing the above-mentioned dopamine hydrochloride modified cerium oxide core-shell abrasive, and its application in chemical mechanical polishing of silicon dioxide. When the abrasive is used to prepare a polishing liquid for SiO2 mechanical polishing, it has a higher removal rate.

[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0008] Silicon dioxide powder was prepared using tetraethyl silicate, hexadecyltrimethylammonium bromide and ammonia water;

[0009] Add water to the cerium salt until the cerium salt is completely dissolved, take out the cerium salt and the silica powder (0.5:1)-(7:1) and disperse them in anhydrous ethanol by ultrasonication to obtain a dispersion;

[0010] The dispersion is mixed with a hexamethylenetetramine aqueous solution and a cerium salt aqueous solution, and the mixture is heated in an oil bath and stirred to react to obtain a mixed solution, the mixed solution is centrifuged, washed with deionized water and anhydrous ethanol, and then dried to obtain a mixed solid, and the mixed solid is calcined to obtain a cerium precursor;

[0011] The cerium precursor is dispersed in a mixed solution of deionized water and ethanol, dopamine hydrochloride and a buffer solution are slowly added, stirred, centrifuged, washed, and dried to obtain;

[0012] The mass ratio of the dopamine hydrochloride to the cerium precursor is (0.5:1)-(7:1).

[0013] In the present invention, the mass ratio of cerium salt to silica powder can be 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 1:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, or 7:1.

[0014] The mass ratio of dopamine hydrochloride to the cerium precursor can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 2:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1.

[0015] In the step of preparing silica powder, ammonia water is used to provide an alkaline environment. Tetraethyl silicate is hydrolyzed under alkaline conditions to produce orthosilicic acid (Si(OH)4). Then the hydroxyl groups between the orthosilicic acid molecules are dehydrated and condensed to form Si-O-Si. Silicic acid is first generated, and then the hydroxyl groups are further dehydrated and condensed to form silica powder, and its microscopic structure is in the form of microspheres.

[0016] In the present invention, hexamethylenetetramine can be hydrolyzed to generate OH - , providing an alkaline environment for the reaction system, and using its slow hydrolysis to make the cerium salt react with OH - The cerium hydroxide is slowly combined to provide a precursor for the cerium hydroxide, and at the same time, it can slowly attach to the silicon dioxide. If sodium hydroxide or other strong alkaline substances are used, the product will be generated immediately, and the coating idea cannot be realized.

[0017] Anhydrous ethanol is used to dissolve the silicon dioxide and wash the silicon dioxide because the anhydrous ethanol can volatilize during the subsequent heating process and does not affect the properties of the cerium oxide abrasive finally generated.

[0018] The feature of dopamine hydrochloride is that it is rich in phenolic hydroxyl groups and amino groups on its surface and is extremely hydrophilic. On the one hand, under alkaline conditions, it can be deposited on the surface of various organic and inorganic materials through oxidative self-polymerization to form a polydopamine coating layer. On the other hand, the excellent adhesion of polydopamine and its rich functional groups such as amino, imine, and catechol can make the surface of nano-CeO2 particles water-soluble. Dopamine hydrochloride can cover the surface of the cerium oxide core-shell structure formed subsequently with a layer of dopamine and polydopamine caused by self-polymerization and adsorption, which is equivalent to forming an organic film on the surface of the cerium oxide core-shell, increasing the water solubility of the nano-abrasive.

[0019] Preferably, as a further specific embodiment, in the method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive, the mass ratio of the dopamine hydrochloride to the cerium precursor is (1:1)-(5:1);

[0020] Preferably, the mass ratio of dopamine hydrochloride to cerium precursor is 1.3:1.

[0021] Preferably, as a further specific embodiment, the mass ratio of the cerium salt to the silicon dioxide powder = (1:1) - (7:1);

[0022] Preferably, the mass ratio of the cerium salt to the silicon dioxide powder is 2:1.

[0023] In the present invention, the mass ratio of cerium salt to silica powder and the mass ratio of dopamine hydrochloride to cerium precursor are limited. The mass ratio of cerium salt to silica powder is limited according to the maximum degree of silica adsorption of cerium oxide. Once it slightly exceeds the limited amount, the coating amount will not change, but cerium oxide / silicon dioxide itself will form particles, and the purpose of coating cannot be achieved; under the condition of the preferred mass ratio of cerium salt to silica powder = (1:1)-(7:1), the coating effect can be guaranteed, but the utilization rate of the raw materials is slightly low at this time, so 2:1 is finally selected as the optimal mass ratio. When dopamine hydrochloride is combined with the cerium precursor and exceeds the limited amount, it will also cause agglomeration, thereby reducing water solubility. Similarly, under the preferred conditions of (1:1)-(5:1), the needs of the present invention can be met, but the utilization rate of the raw materials is slightly low at this time, so 1.3:1 is selected as the optimal mass ratio.

[0024] Preferably, as a further specific embodiment, the cerium salt is a mixture of any one or more of cerium nitrate, cerium chloride, cerium octoate, ammonium cerium nitrate, ammonium cerium carbonate, ammonium cerium sulfate, cerium sulfide and cerium sulfate.

[0025] In the present invention, soluble cerium salts and / or slightly soluble cerium salts are preferred. Insoluble cerium salts are difficult to react with hexamethylenetetramine to generate OH groups by hydrolysis. - The generation of cerium hydroxide under low-temperature stirring is not conducive to the subsequent growth of cerium oxide.

[0026] Preferably, as a further specific embodiment, the buffer solution is a mixture of any one or more of sodium bicarbonate, BIS-TRIS, TRIS, and potassium dihydrogen phosphate solution;

[0027] Preferably, the mass ratio of the solute in the buffer to the cerium precursor = (0.5:1) - (5:1);

[0028] Preferably, the mass ratio of the solute in the buffer to the cerium precursor = (1:1) - (3:1);

[0029] Preferably, the mass ratio of the solute in the buffer to the cerium precursor is 2:1.

[0030] In the present invention, the mass ratio of the solute to the cerium precursor in the buffer solution can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 1:1, 1:1, 2:1, 3:1, 4:1, or 5:1.

[0031] The amount of buffer is an important factor in maintaining the polishing performance and good water dispersibility of the abrasive, so the amount of buffer needs to be limited. When the amount of buffer is large, the content of solute in the buffer will increase accordingly, and the solute will inhibit the polymerization reaction of dopamine hydrochloride on the surface of the abrasive, resulting in a decrease in the number of dopamine coated on the surface of the abrasive, reducing the dispersibility of the abrasive in water; when the amount of buffer is small, the content of solute in the buffer will decrease accordingly, which will lead to excessive polymerization of polyhydrochloric acid dopamine, making it unable to coat the surface, aggravating the agglomeration between the abrasives, and causing the reduction of its polishing performance. Therefore, it is preferred that the mass ratio of the solute in the buffer to the cerium precursor = (0.5:1)-(5:1) can well take into account dispersibility and solubility, preferably the mass ratio of the solute in the buffer to the cerium precursor = (1:1)-(3:1), and more preferably the mass ratio of the solute in the buffer to the cerium element in the cerium salt = 2:1, which can achieve the technical effect of the present invention.

[0032] In addition, one buffer solution may be selected alone, or multiple buffer solutions may be selected and mixed without affecting the final effect. In the present invention, a mixture of BIS-TRIS and sodium bicarbonate is selected.

[0033] The stirring time after adding dopamine hydrochloride and buffer solution is 2-48 h. When dopamine hydrochloride is coated on the core-shell material, as the reaction time increases, the PDA film on the surface of the core-shell abrasive becomes thicker and rougher, but the water solubility becomes better and better accordingly. However, it will cause its size to become larger and larger.

[0034] Preferably, as a further specific embodiment, the concentration of the hexamethylenetetramine aqueous solution is 0.01 mol / L-1.0 mol / L; the temperature of the oil bath is 30°C-100°C;

[0035] Preferably, the concentration of the hexamethylenetetramine aqueous solution is 0.1 mol / L;

[0036] Preferably, the temperature of the oil bath is 30°C.

[0037] In the present invention, the concentration of the hexamethylenetetramine aqueous solution can be 0.01mol / L, 0.02mol / L, 0.03mol / L, 0.04mol / L, 0.05mol / L, 0.06mol / L, 0.07mol / L, 0.08mol / L, 0.09mol / L, 0.1mol / L, 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.4mol / L, 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L.

[0038] In the present invention, the concentration of the hexamethylenetetramine aqueous solution needs to be limited. A low concentration of hexamethylenetetramine will reduce the yield of cerium oxide, while a high concentration will result in the decomposition of soluble cerium salt and hexamethylenetetramine to produce NH4 + Combined with the formation of cerium ammonium salt, the formation of cerium oxide is inhibited. In the reaction system of the present invention, the concentration of the hexamethylenetetramine aqueous solution is preferably 0.01 mol / L-1.0 mol / L, at which the yield of cerium oxide is high, and more preferably the concentration of the hexamethylenetetramine aqueous solution is 0.1 mol / L, at which the yield of cerium oxide is the highest.

[0039] In the present invention, the temperature of the oil bath affects the growth of cerium oxide on the surface of silicon dioxide. When the temperature of the oil bath is low, a low temperature environment is formed, and the low temperature inhibits the hydrolysis of hexamethylenetetramine and inhibits the reaction of cerium salt with OH. - The decomposition of cerium hydroxide generated by the combination of silica / mesoporous silica and cerium oxide prevents the formation of cerium oxide; and high temperature causes the self-agglomeration of silica / mesoporous silica and cerium oxide, making it impossible to form a mesoporous silica composite abrasive coated with cerium oxide. Therefore, it is necessary to limit the temperature of the oil bath. When the oil bath temperature is 30°C-100°C, preferably 30°C, the technical effect of the present invention can be achieved.

[0040] Preferably, calcination is required in the process of preparing the silicon dioxide powder, and the calcination temperature is 200°C-1000°C;

[0041] The mass ratio of ammonia water to tetraethyl silicate is (1:1)-(1:10);

[0042] Preferably, the calcination temperature is 550°C;

[0043] Preferably, the mass ratio of the ammonia water to tetraethyl silicate is 2:1.

[0044] In the process of preparing silica powder, the calcination temperature needs to be controlled. To a certain extent, high temperature is conducive to the formation of silica. The silica formed by higher calcination temperature is conducive to the formation of cerium oxide core-shell structure and the growth of crystal form. When the calcination temperature is low, it is difficult to form silica with core-shell structure; when the calcination temperature is too high, it will cause silica to deform, and eventually make the core-shell structure particles formed too large or the structure collapse.

[0045] When tetraethyl silicate is in a suitable content range, the size of the silicon spheres finally generated can be fixed between 250 nm and 300 nm, which is beneficial to the polishing of the composite abrasive.

[0046] The present invention also provides a method for preparing dopamine hydrochloride modified cerium oxide core-shell abrasive, and application of the cerium oxide core-shell abrasive prepared by the method in chemical mechanical polishing of silicon dioxide.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] The nano-abrasive prepared by the preparation method has a core-shell structure, adjustable size, high hydrophilicity and bio-miscibility, and high removal rate; the present invention combines mesoporous core-shell with compatible dopamine and applies it to the polishing field, and its process is novel and has certain foresight. The core-shell structure cerium oxide nano-abrasive prepared by the preparation method of the present invention has high water solubility, and the polishing liquid prepared by using this abrasive has a removal rate of up to 0.1458 mg / min. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 : SEM image of SiO2@CeO2@PDA sample in Example 1.

[0050] Figure 2 : XRD patterns of SiO2@CeO2@PDA and SiO2@CeO2 samples in Example 1.

[0051] Figure 3: Contact angle diagram of SiO2@CeO2 and SiO2@CeO2@PDA samples in Example 1. DETAILED DESCRIPTION

[0052] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0053] Example 1

[0054] Preparation of SiO2 microspheres.

[0055] 0.4 g hexadecyltrimethylammonium bromide and 1.8 g ammonia water were dissolved in 120 mL of a mixed solution of deionized water and ethanol (water:ethanol=5:1). Tetraethyl silicate ethanol solution (0.9 g TEOS, 30 mL) was slowly added to the mixed solution, stirred in a water bath at 30 °C for 2 h, centrifuged, washed with deionized water and anhydrous ethanol, and dried in an oven at 80 °C overnight to obtain a white powder. The white powder was calcined at 550 °C in air for 4 h to obtain monodispersed SiO2 microspheres.

[0056] Preparation of SiO2@CeO2 cerium precursor

[0057] 0.1 g of the prepared SiO2 microspheres were ultrasonically dispersed in 25 mL of anhydrous ethanol, and then 20 mL of Ce(NO3)3 (0.2 g) and hexamethylenetetramine aqueous solution (0.28 g) were added in sequence. The mixed solution was placed in a 75 ℃ oil bath and stirred for 2 h. The mixed solution was centrifuged, washed with deionized water and anhydrous ethanol, and dried at 80 ℃ to obtain a dark brown solid. The solid was calcined at 650 ℃ for 2 h to obtain a SiO2 / CeO2 cerium precursor.

[0058] Preparation of SiO2 / CeO2@PDA materials

[0059] 0.1 g of SiO2 / CeO2 cerium precursor was ultrasonically dispersed in a mixed solution of 40 mL of deionized water and ethanol (water: ethanol = 3:1), and stirred in a 30°C water bath. After adding 0.2 g of Bis-tris containing solute mass to the above solution and stirring for 30 minutes, 10 mL of dopamine hydrochloride aqueous solution (0.13 g) was quickly added to the above mixed solution. When the color of the solution turned dark brown, the timing began and stirring was continued for 8 hours. After centrifugation and washing with water, the SiO2@CeO2@PDA sample was obtained, such as Figure 1 The prepared samples are spherical in shape, uniform in size, and have a rough surface. Figure 2 In the results, the peaks of SiO2@CeO2@PDA and SiO2@CeO2 samples are consistent with those of the standard card of CeO2 (JCPDS 78-0694), indicating that the modification did not change the crystal structure of CeO2. Figure 3 It can be seen that the contact angles of SiO2@CeO2@PDA and SiO2@CeO2 samples are 34° and 70° respectively. It can be seen that after modification with dopamine hydrochloride, its contact angle becomes smaller, proving that its hydrophilicity increases.

[0060] Polishing experiment

[0061] The polishing experiment was carried out using UNIPOL-1200S automatic pressure grinding and polishing machine produced by Shenyang Kejingzi Company, and the polishing pad model was IC1010 (purchased from Dow Electronic Materials, USA). The polishing process parameters are as follows: the fixed polishing pressure is 6.0 kg (1 kg = 0.1MPa), the polishing head and the polishing disc speed are 87 r / min and 93 r / min respectively, the polishing liquid flow rate is 300 mL / min, and the polishing time is 1 min. The polishing liquid composition: cerium oxide solution (solid content 7.5%), dispersant, pH adjuster (CA and TEAH).

[0062] The film thickness before and after polishing was measured with a film thickness meter, and the thickness value was recorded. The removal rate was calculated by the formula (MRR = Δh / t) and the weight difference.

[0063] In the present invention, embodiment 1 is the best solution.

[0064] Note: The higher the removal rate, the better. After calculation, the removal rate should not exceed 0.35 mg / min. Too high a removal rate may lead to higher mechanical scratches, while too low a removal rate cannot achieve polishing. Therefore, the removal rate is best kept between 0.1mg / min-0.15mg / min. Within this range, the higher the removal rate, the better. At the same time, in order to ensure the coverage rate, the diameter of the silica microspheres is between 250nm-300nm as the best choice.

[0065] Example 2

[0066] The specific implementation steps are consistent with those in Example 1, except that the mass ratio of ammonia water and tetraethyl silicate is changed, as follows:

[0067] When the mass ratio is 1:1, the mass of tetraethyl silicate is 0.45 g, and the prepared SiO2@CeO2@PDA1 nanoabrasive is obtained;

[0068] When the molar ratio is 1:5, the mass of tetraethyl silicate is 2.25 g, and the nano-abrasive SiO2@CeO2@PDA2 is prepared;

[0069] When the molar ratio is 1:10, the mass of tetraethyl silicate is 4.5 g, and the nano-abrasive SiO2@CeO2@PDA3 is prepared;

[0070] The prepared cerium oxide nanoabrasive was prepared into a polishing liquid for mechanical polishing. The removal rate was measured using the polishing experiment in Example 1. The experimental results are shown in Table 1.

[0071] Table 1: Effects of different ammonia / tetraethyl silicate doping ratios on the size and removal rate of cerium oxide nanoabrasives

[0072] .

[0073] Comparing Example 2 with Example 1, it can be seen that the change in the ratio of ammonia water and tetraethyl silicate affects the size of the cerium oxide nanoabrasive. When the content of tetraethyl silicate is within a suitable range, the size of the silicon sphere is fixed, and when the diameter of the silicon dioxide microsphere is between 250 nm and 300 nm, it is more conducive to coating and also more conducive to the polishing of the composite abrasive. After comprehensive selection, the size of 300 nm was finally selected as the optimal size.

[0074] In Scheme 1 of Example 2, the content of tetraethyl silicate is low, and the content of silicon element therein is also low, so the size of the prepared abrasive is relatively small, only 110 nm. It can be seen that when the ratio of ammonia water and tetraethyl silicate is lower than 1:1, the size of the generated abrasive is less than 110 nm. If the size of the abrasive is too small, it will not fully play the role of the SiO2 elastic core, thereby affecting its polishing performance.

[0075] In Example 2, Scheme 3, the content of tetraethyl silicate is high, and the content of silicon is also high. At this time, the size of the abrasive prepared is 400 nm. It can be seen that when the ratio of ammonia water to tetraethyl silicate is greater than 1:10, the size of the final abrasive is greater than 400 nm. The size of the abrasive is too large, and the silicon dioxide substrate is too large, which will cause the polishing liquid to scratch the device, resulting in a decrease in its various physical properties. Therefore, the mass ratio of ammonia water to tetraethyl silicate is finally controlled between (1:1)-(1:10).

[0076] Example 3

[0077] The specific implementation steps are consistent with those in Example 1, except that only the mass of the cerium precursor is changed. In this preparation process, since the mass ratio of ammonia water and tetraethyl silicate remains unchanged, the size of the silica microspheres finally generated is maintained at 300 nm. The specific changes are as follows:

[0078] Scheme ①: When the mass of the cerium precursor is 0.2 g, the mass ratio of the solute in the buffer solution to the cerium precursor is 0.5:1; the mass ratio of dopamine hydrochloride to the cerium precursor is 0.65:1.

[0079] Scheme ②: When the mass of the cerium precursor is 0.1 g, the mass ratio of the solute in the buffer solution to the cerium precursor is 1:1; the mass ratio of dopamine hydrochloride to the cerium precursor is 1.3:1.

[0080] Scheme ③: When the mass of the cerium precursor is 0.05 g, the mass ratio of the solute in the buffer solution to the cerium precursor is 2:1; the mass ratio of dopamine hydrochloride to the cerium precursor is 2.6:1.

[0081] Scheme ④: When the mass of the cerium precursor is 0.02 g, the mass ratio of the solute in the buffer solution to the cerium precursor is 5:1; the mass ratio of dopamine hydrochloride to the cerium precursor is 6.5:1.

[0082] Scheme ⑤: When the mass of the cerium precursor is 0.018 g, the mass ratio of the solute in the solution to the cerium precursor is 5.4:1; the mass ratio of dopamine hydrochloride to the cerium precursor is 7:1.

[0083] Scheme ⑥: When the mass of the cerium precursor is 0.1 g, the mass of dopamine hydrochloride is 0.13 g, and the solute in the buffer solution is 0.3 g, the mass ratio of the solute in the buffer solution to the cerium precursor is 3:1; the mass ratio of dopamine hydrochloride to the cerium precursor is 1.3:1.

[0084] Solution ⑦: When the mass of the cerium precursor is 0.1 g, the mass of dopamine hydrochloride is 0.1 g, and the solute in the buffer solution is 0.2 g, the mass ratio of the solute to the cerium precursor in the buffer solution is 2:1, and the mass ratio of dopamine hydrochloride to the cerium precursor is 1:1.

[0085] Scheme ⑧: When the mass of the cerium precursor is 0.1 g, the mass of dopamine hydrochloride is 0.05 g, and the solute in the buffer solution is 0.2 g, the mass ratio of the solute to the cerium precursor in the buffer solution is 2:1, and the mass ratio of dopamine hydrochloride to the cerium precursor is 1:1.

[0086] The prepared cerium oxide nanoabrasive was prepared into a polishing liquid for mechanical polishing. The removal rate and polishing amount were measured using the polishing experiment in Example 1. The experimental results are shown in Table 2.

[0087] Table 2: Effect of different cerium precursor dosage on the polishing rate of cerium oxide nanoabrasive

[0088] .

[0089] The experimental data of Example 3 show that the amount of different cerium precursors used has an important influence on the polishing performance of cerium oxide nanoabrasives. It can be seen from the comparison of Example 3 Scheme ① with Example 1 that when the mass ratio of solute to cerium salt in the buffer solution is 0.5:1, the content of solute in the buffer solution is less, and the removal rate is 0.1613 mg / min. It can be inferred that when the content of solute in the buffer solution is lower than this content, the removal rate will be too low. The reason is that when the content of buffer solution is too low, dopamine hydrochloride will polymerize, resulting in abrasive agglomeration. Therefore, the mass ratio of solute to cerium salt in the final buffer solution cannot be lower than 0.5:1.

[0090] From the comparison of Example 3 Scheme ⑤ with Example 1, it can be seen that when the mass ratio of the solute to the cerium salt in the buffer solution is 5.4:1, the content of the solute in the buffer solution is relatively large, and the removal rate at this time is 0.0798 mg / min. It can be inferred that when the content of the solute in the buffer solution is high, the removal rate will also be reduced. The reason is that more solute will inhibit the polymerization of dopamine hydrochloride on the surface of the abrasive, thereby reducing the hydrophilicity of the abrasive and further affecting its removal rate. Therefore, the mass ratio of the solute to the cerium salt in the final buffer solution cannot be higher than 5:1.

[0091] When selecting the quality of the cerium precursor, the relationship between the cerium precursor and dopamine hydrochloride should also be taken into account. When the content of the cerium precursor is within an appropriate range, it is more conducive to the polishing of the composite abrasive. By comparing Example 3, Scheme ③ and Example 1, it can be seen that when only the content of dopamine hydrochloride is increased while other factors remain unchanged, the removal rate increases, but the removal performance deteriorates. The reason is that excessive dopamine hydrochloride will cause agglomeration, which in turn reduces its physical properties.

[0092] By comparing Example 1 with Scheme 7 of Example 3 and Scheme 8 of Example 3, it can be found that when the mass ratio of the solute to the cerium salt in the buffer solution is fixed and the mass of the cerium precursor is increased, the removal rate will be increased accordingly. The reason is that with the increase of the cerium precursor, Ce 3+ The overall content increased. 3+ The ions can not only weaken and stretch the Si-O bonds and promote the formation of the glass hydration layer, but also promote the formation of Ce-O-Si bonds which are much stronger than Si-O-Si, thereby effectively improving the polishing performance of the composite abrasive on the glass substrate.

[0093] Therefore, the increase of trivalent cerium ion content on the composite abrasive surface is one of the reasons for improving the glass CMP performance.

[0094] Example 4

[0095] The specific implementation method is consistent with Example 1, only the mass ratio of silica powder and cerium salt is changed. Since the mass ratio of ammonia water and tetraethyl silicate remains unchanged, the size of the silica microspheres finally generated is maintained at 300 nm. The specific changes are as follows:

[0096] When the mass of silicon dioxide is 2 g, the mass of cerium salt is 0.2 g. At this time, the mass ratio of cerium salt to silicon dioxide powder is 0.1:1. 0.1 SiO2@CeO2@PDA

[0097] When the mass of silicon dioxide is 1 g, the mass of cerium salt is 0.2 g. At this time, the mass ratio of cerium salt to silicon dioxide powder is 0.2:1. 0.2 SiO2@CeO2@PDA;

[0098] When the mass of silicon dioxide is 0.2 g, the mass of cerium salt is 0.2 g, and the mass ratio of cerium salt to silicon dioxide powder is 1:1, and 1SiO2@CeO2@PDA is obtained;

[0099] When the mass of silicon dioxide is 0.1 g, the mass of cerium salt is 0.2 g, and the mass ratio of cerium salt to silicon dioxide powder is 2:1, and 2SiO2@CeO2@PDA (Example 1) is obtained;

[0100] When the mass of silica is 0.028 g, the mass of cerium salt is 0.2 g, and the mass ratio of cerium salt to silica powder is 7:1, and 7SiO2@CeO2@PDA is obtained;

[0101] When the mass of silicon dioxide is 0.02 g, the mass of cerium salt is 0.2 g, and the mass ratio of cerium salt to silicon dioxide powder is 10:1, we get 10 SiO2@CeO2@PDA;

[0102] When the mass of silicon dioxide is 0.013 g, the mass of cerium salt is 0.2 g. At this time, the mass ratio of cerium salt to silicon dioxide powder is 15:1. 15 SiO2@CeO2@PDA;

[0103] The prepared cerium oxide nanoabrasive was prepared into a polishing liquid for mechanical polishing. The removal rate and polishing amount were measured using the polishing experiment in Example 1. The experimental results are shown in Table 3.

[0104] Table 3: Changes in removal rate at different mass ratios of silica to cerium salt

[0105] .

[0106] By comparing Scheme 1 of Example 4 with Example 1, it can be seen that when silicon dioxide is excessive, the removal rate will be reduced to 0.0045 mg / min. The main reason is that when the amount of silicon dioxide used is large, the content of cerium element will be correspondingly low, the coating efficiency will be low (that is, the effective coating amount will be reduced), and the raw material (silicon dioxide / cerium dioxide) will agglomerate itself, thereby reducing the removal rate.

[0107] By comparing Example 4, Scheme 6 and Example 1, it can be seen that when the silicon dioxide content is low, the excess cerium salt cannot be coated, resulting in waste of cerium salt, low raw material utilization, and affected coating effect; from the data, although the removal rate increases, the removal performance decreases.

[0108] Therefore, in actual use, the ratio between the two needs to be limited to ensure the coating effect of cerium dioxide and silicon dioxide.

[0109] Example 5

[0110] The specific implementation method is the same as Example 1, only the calcination temperature is changed. Since the mass ratio of ammonia water and tetraethyl silicate remains unchanged, the size of the silica microspheres finally generated is maintained at 300 nm. The specific changes are as follows:

[0111] When the calcination temperature was 100 °C, SiO2@CeO2@PDA(100) was prepared;

[0112] When the calcination temperature was 200 °C, SiO2@CeO2@PDA(200) was prepared;

[0113] When the calcination temperature is 400 °C, SiO2@CeO2@PDA(400) is prepared;

[0114] When the calcination temperature is 600 °C, SiO2@CeO2@PDA(600) is prepared;

[0115] When the calcination temperature is 1000 °C, SiO2@CeO2@PDA(1000) is prepared;

[0116] When the calcination temperature is 1500 °C, SiO2@CeO2@PDA(1500) is prepared;

[0117] The removal rate was determined using the polishing experiment in Example 1. The experimental results are shown in Table 4.

[0118] Table 4: Effect of different calcination temperatures on the polishing rate of multi-shell nanoabrasives

[0119] .

[0120] Can find out that calcining temperature affects the polishing rate of shell nano abrasive by embodiment 5 experimental data.When calcining temperature is 100 ℃, calcining temperature is too low, can't form silicon dioxide, reaction can't be carried out, therefore can't coat, and the result of obtained removal rate is meaningless.To a certain extent, high temperature is beneficial to the generation of cerium oxide core-shell structure and the growth of crystal formation, can find out by comparing 550 ℃ and 1500 ℃ data, too high temperature can reduce removal rate equally, affects its removal performance, its reason is that temperature is too high and causes the particle in template method synthesis core-shell structure process to be too large, thereby makes its polishing rate decline.Therefore need to limit to ensure the formation of core-shell structure for calcining temperature in this process.

[0121] Example 6

[0122] The specific implementation method is the same as that of Example 1, except that only the concentration of the methylenetetramine aqueous solution is changed. Since the mass ratio of ammonia water and tetraethyl silicate remains unchanged, the size of the silica microspheres finally generated is maintained at 300 nm. The specific changes are as follows:

[0123] When the concentration of the hexamethylenetetramine aqueous solution is 0.005 mol / L, the mass of the hexamethylenetetramine used is 0.014 g;

[0124] When the concentration of the hexamethylenetetramine aqueous solution is 0.01 mol / L, the mass of the hexamethylenetetramine used is 0.028 g;

[0125] When the concentration of the hexamethylenetetramine aqueous solution is 0.1 mol / L, the mass of the hexamethylenetetramine used is 0.28 g;

[0126] When the concentration of the hexamethylenetetramine aqueous solution is 0.5 mol / L, the mass of the hexamethylenetetramine used is 1.4 g;

[0127] When the concentration of the hexamethylenetetramine aqueous solution is 1.0 mol / L, the mass of the hexamethylenetetramine used is 2.8 g;

[0128] When the concentration of the hexamethylenetetramine aqueous solution is 1.5 mol / L, the mass of the hexamethylenetetramine used is 4.2 g.

[0129] The removal rate was determined using the polishing experiment in Example 1. The experimental results are shown in Table 5.

[0130] Table 5: Effect of different hexamethylenetetramine aqueous solution concentrations on the polishing rate of multi-shell nanoabrasives

[0131] .

[0132] From the experimental data of Example 6, it can be seen that the removal rate is better when the concentration of the hexamethylenetetramine aqueous solution is 0.01mol / L-1.0mol / L. When the hexamethylenetetramine aqueous solution is lower than 0.01mol / L, the cerium oxide production is too low and it is difficult to measure its removal rate. The experimental results obtained are meaningless. When the concentration of the hexamethylenetetramine aqueous solution affects the polishing rate of the shell nanoabrasive, the OH produced by the hydrolysis of low-concentration hexamethylenetetramine - It is not enough to provide a suitable alkaline environment for the formation of cerium hydroxide, resulting in too low a yield of cerium oxide. It can be seen from the experimental data that high concentrations will also reduce the removal rate because the NH4 + The combination forms cerium ammine salt, which inhibits the formation of cerium oxide, thereby causing a decrease in the polishing rate of the nanoabrasive.

[0133] Example 7

[0134] The specific implementation method is the same as that of Example 1, except that the stirring time after adding dopamine hydrochloride and the buffer solution is changed, and the stirring time is 2 h, 16 h, 24 h, and 48 h.

[0135] The removal rate was determined using the polishing experiment in Example 1. The experimental results are shown in Table 6.

[0136] Table 6: Effect of different stirring times on the polishing rate of multi-shell nanoabrasives

[0137] .

[0138] It can be seen from the experimental data of Example 4 that the stirring time affects the polishing rate of the shell nanoabrasive. When dopamine hydrochloride is coated with the core-shell material, as the reaction time increases, the PDA film on the surface of the core-shell abrasive becomes thicker and thicker, becoming more and more rough, but the water solubility will become better and better accordingly, which will increase the removal rate to a certain extent. However, too long a time will make the particles larger and affect their removal rate. Therefore, it is necessary to limit the stirring time.

[0139] Comparative Example 1

[0140] When ammonia water is used for cerium oxide coating reaction, the reaction cannot proceed and the abrasive cannot be prepared.

[0141] Comparative Example 2

[0142] Silica core particles are used, combined with cerium oxide, and a conditioner, corrosion inhibitor, oxidant, chelating agent and surfactant are added for reaction.

[0143] The silicon dioxide core particles used in Comparative Example 2 are hollow particles prepared in this embodiment. Therefore, the particles in Comparative Example 2 cannot be coated, and the removal rate is not as good as that of the present invention.

[0144] Based on the above data, we can draw the following conclusions:

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a dopamine hydrochloride modified cerium oxide core-shell abrasive, characterized in that: The steps include: Preparation of silica powder using tetraethyl silicate, hexadecyltrimethylammonium bromide and ammonia water; Add water to the cerium salt until the cerium salt is completely dissolved, take out the silica powder with a mass ratio of cerium salt to silica powder of (2:1) to (7:1), and ultrasonically disperse it in anhydrous ethanol to obtain a dispersion; The dispersion is mixed with a hexamethylenetetramine aqueous solution and a cerium salt aqueous solution, and the mixture is heated in an oil bath and stirred to react to obtain a mixed solution, the mixed solution is centrifuged, washed with deionized water and anhydrous ethanol, and then dried to obtain a mixed solid, and the mixed solid is calcined to obtain a cerium precursor; The cerium precursor is dispersed in a mixed solution of deionized water and ethanol, dopamine hydrochloride and a buffer solution are slowly added, stirred, centrifuged, washed, and dried to obtain; The mass ratio of dopamine hydrochloride to cerium precursor = (0.5:1) - (7:1); The mass ratio of the solute in the buffer to the cerium precursor is (0.5:1)-(5:1).

2. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 1, characterized in that: The mass ratio of the dopamine hydrochloride to the cerium precursor is (1:1)-(5:1).

3. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 2, characterized in that: The mass ratio of dopamine hydrochloride to the cerium precursor is 1.3:

1.

4. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 1, characterized in that: The buffer solution is a mixture of any one or more of sodium bicarbonate, BIS-TRIS, TRIS, and potassium dihydrogen phosphate solution.

5. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 4, characterized in that: The mass ratio of the solute in the buffer to the cerium precursor is (1:1)-(3:1).

6. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 5, characterized in that: The mass ratio of the solute in the buffer to the cerium precursor is 2:

1.

7. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 1, characterized in that: The concentration of the hexamethylenetetramine aqueous solution is 0.01 mol / L-1.0 mol / L; the temperature of the oil bath is 30°C-100°C.

8. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 7, characterized in that: The concentration of the hexamethylenetetramine aqueous solution is 0.1 mol / L; The temperature of the oil bath was 30°C.

9. The method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to claim 1, characterized in that: The process of preparing the silicon dioxide powder requires calcination, and the calcination temperature is 200°C-1000°C; The mass ratio of ammonia water to tetraethyl silicate is (1:1)-(1:10).

10. Use of the cerium oxide core-shell abrasive prepared by the method for preparing the dopamine hydrochloride modified cerium oxide core-shell abrasive according to any one of claims 1 to 9 in chemical mechanical polishing of silicon dioxide.

Citation Information

Patent Citations

  • Preparation and use of cerium oxide / silicon oxide compound abrasive

    CN101475791A

  • Slurry composition

    KR101483451B1